THE EFFECTS OF ROOM SERVICE TO IMPROVE PATIENTS’ FOOD SATISFACTION AND FOOD ACCEPTANCE - Iqbal, Muhammad; Susetyowati, Susetyowati; Purba, Martalena Br (GIZI INDONESIA, 2016)
The improvement of patients’ food satisfaction and acceptance in the hospitals is primarily needed in the food service  system.  Room service is a new concept in the food service area. This study aims to compare the effects of two different types of food service systems; room service and conventional service system. The study with quasi-experimental design is conducted to the subject of 66 inpatients who were taken using a quota sampling method. Subjects were divided into different groups, the treatment groups (room service) and control groups (conventional). Leftover food between groups was compared for 9 large meals to determine acceptability. Food satisfaction is measured on the last day with using questionnaire. The study was conducted in April-June 2014. Chi-Square test and logistic regression were used for analysis of research data. There were significant differences food satisfaction (RR=4.6; p=0.0001) and food acceptance (RR=1.94; p=0.0488) between control and treatment group. The logistic regression test showed that room service group had higher food satisfaction and food acceptance level than control group after controlling confounding factors, which were 12,11 times (95% CI 3,593 – 37,219) and 2,38 times (95% CI 0,68-8,31), respectively. The room service increases food satisfaction and food acceptance of patients compared with conventional systems.